Identification of Regional Factors Affecting Management of Territories: Formation of Residence and Social Infrastructure System in Urban and Rural Settlements in Kazakhstan - KORNILOVA, Alla Aleksandrovna; MAMEDOV, Seimur Etibar ogly; KARABAYEV, Gani Aitbayevich; KHOROVETSKAYA, Yevgeniya Mikhaylovna; LAPTEVA, Irina Vladimirovna (Journal of Environmental Management and Tourism, 2022)
Ensuring the socio-economic development of a country and its territories as a key area of public administration includes the choice of directions and approaches to improving the efficiency of management processes. In the study, the authors focused on the processes of settlement, social infrastructure, and architectural and planning organization of populated areas, which are important factors influencing the development of territories. The article aims at developing a conceptual and theoretical model of the management system of the settlement and social infrastructure in the Republic of Kazakhstan. To attain this objective, the following methods were used: the analysis of documents (archives and historical materials), architectural design methods, socio-economic and demographic analysis, SWOT analysis, and population survey. Data collection was carried out during the expedition and from 1991 to 2020 based on monitoring the forms and methods of managing territories in changing socio-economic conditions, which contributes to the improvement of the settlement system of urban and rural settlements, as well as on the way of life of the population, and the impact of historical, climatic, natural, and socio-economic factors on the spatial organization in the territory. Based on the study results, a conceptual and theoretical model of organization management in the settlement system and social infrastructure of Kazakhstan was developed which reduces the level of urbanization in rural areas and increases the comfort of living of the population and the opportunities for attracting tourists.